Learning model and evaluation: An implementation case-based learning and tech-based holistic assessment rubrics in English learning - Santoso, Yan Imam; Shofyana, Maila Huda; Anasa, Firyal Afaf; Aditama, Madya Giri (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this study is to find a learning protocol that implements case-based and technological-based integrated assessment requirements for English language learning in classrooms. The research used qualitative design and phenomenological approaches. The researcher conducted a data survey of the assessment of the focus group discussions (FGDs) to align teacher perceptions of case-based learning (CBL) and technology-based holistic assessment rubrics (TBHAR) in English teaching and learning. According to the data, 80% of people learn CBL and TBHAR in English. The average difficulty of implementing CBL is moderate, which means that it can be challenging but manageable. Analysis of survey and interview data came to a decisive conclusion that this method requires constant support and broad understanding to succeed in implementation. In short, combination of case-based learning and tech-based holistic assessment effectively enhances students’ critical thinking and problem-solving skills in English learning. The research findings highlight its effectiveness in fostering deeper understanding and practical application in English learning. These methods provide a comprehensive approach to address challenges in language education.